Ecophysiological Studies on Saltwort in the Indian Desert Sher Mohammed and David N Sen - Mohammed, Sher; Sen, David N (Annals of Arid Zone, 2016)
Saltworl is a halophyte growing naturally in the highly saline tracts of the Indian desert. This investigation was conducted to determine sail resistance. soil-plant relationships. metabolic process and survival of the saltworl (Suaeda fruitcosa (L.) Forsk.) as influenced by salinity. This species exhihibited higher sugar and protein contents in rainy season and higher chlorophyll under salt stress. Proline accumulation was higher in the winter followed by summer and lowest in the rainy season. All the elements viz. Na, K. Ca and CI studied in plant and soil did not follow a definite pattern.